The Influence of Animated Film Media on the Reading Interest of Class II Madrasah Ibtidaiyah - Jannah, Raudatul; Maufur, Syibli; Alfiani, Dwi Anita (UIN Siber Syekh Nurjati Cirebon, 2024)
This study aims to describe the influence of animated film media on the reading interest of grade II MI students. This study uses a quantitative approach with a pre-experimental method, and a one-shot case study design. The population of this study is grade II students, the sample in this study is 26 students participating in this study. Data collection techniques with observation and questionnaires. Indicators of reading interest are the enjoyment of reading books, the need to read books, interest in books, the desire to read books, the desire to find reading books. With 16 statements of reading interest questionnaires, this research instrument has passed the validity test, the reliability test and was approved to measure the reading interest of grade II students. The data analysis techniques used in this study are descriptive statistical analysis and inferential analysis. The results of the study provide information on the impact of animated film media on a 35% increase in reading with good scores. This is shown by the results of the hypothesis test that the application of animated film media has a positive effect on reading interest. It can be proven by the p-value (sig.t) of < 0.05, which is 0.000 < 0.05, and the tcal value of > ttable is 0.551 > 0.389. This means that Ho was rejected and Ha was accepted, thus there was an influence of animated film media on MI's class II reading interest.Keywords: Animated Film Media, Reading Interest